Clinical manifestations and pregnancy outcomes of COVID-19 in indonesian referral hospital in central pandemic area - Muhammad Ilham Aldika Akbar, - (Korean Society of Obstetrics and Gynecology, 2021)
Objectives Data on the clinical manifestations and pregnancy outcomes of pregnant women with COVID-19 are limited, particularly in developing countries. The aim of this study was to analyze the clinical manifestations and pregnancy outcomes in COVID-19 maternal cases in a large referral hospital in Indonesia. Methods This study used a prospective cohort design and included all pregnant women with suspected COVID-19. Subjects were divided into COVID-19 and non-COVID-19 groups based on the results of real-time polymerase chain reaction (RT-PCR) for SARS-CoV-2. Clinical characteristics, laboratory results, and pregnancy outcomes were compared between the two groups. Results Of the 141 suspected maternal cases, 62 cases were COVID-19-confirmed (43.9%), while 79 suspected cases were negative (56.1%). The clinical manifestations and laboratory findings between the two groups were not significantly different (P>0.05). However, the maternal mortality directly caused by COVID-19 was significantly higher than that in the non-COVID-19 group (8.3% vs. 1.3%; P=0.044; OR 6.91, 95% CI: 0.79-60.81). Conclusion The clinical manifestations and laboratory results of suspected pregnant women with positive and negative RT-PCR COVID-19 results were similar. However, within the Indonesian setting, COVID-19 significantly increases the risk of maternal death through both direct and indirect factors.